2003
DOI: 10.1007/s00221-003-1392-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying interlimb transfer of visuomotor rotations

Abstract: We previously reported that opposite arm training improved the initial direction of dominant arm movements, whereas it only improved the final position accuracy of non-dominant arm movements. We now ask whether each controller accesses common, or separate, short-term memory resources. To address this question, we investigated interlimb transfer of learning for visuomotor rotations that were directed oppositely [clockwise (CW)/counterclockwise (CCW)] for the two arms. We expected that if information obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
88
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 27 publications
(46 reference statements)
14
88
1
1
Order By: Relevance
“…The idea that movement trajectory and final position are differentially controlled is also consistent with studies that have examined adaptation to novel forces (DiZio & Lackner, 1995;Lackner & DiZio, 1994) and visuomotor rotations (Sainburg & Wang, 2002;Wang & Sainburg, 2003. In the studies by Lackner and DiZio (DiZio & Lackner, 1995;Lackner & DiZio, 1994), participants reached to a target when adapting to Coriolis force fields, without any visual feedback.…”
Section: Differential Control Of Trajectory and Positionsupporting
confidence: 65%
See 1 more Smart Citation
“…The idea that movement trajectory and final position are differentially controlled is also consistent with studies that have examined adaptation to novel forces (DiZio & Lackner, 1995;Lackner & DiZio, 1994) and visuomotor rotations (Sainburg & Wang, 2002;Wang & Sainburg, 2003. In the studies by Lackner and DiZio (DiZio & Lackner, 1995;Lackner & DiZio, 1994), participants reached to a target when adapting to Coriolis force fields, without any visual feedback.…”
Section: Differential Control Of Trajectory and Positionsupporting
confidence: 65%
“…This clearly suggests that trajectory and position seem to be differentially controlled. More recent studies investigating interlimb transfer of adaptation to visuomotor rotations have revealed similar distinctions in transfer of trajectory and final position information across limbs, thus lending further support to the idea that these features may be differentially encoded (Sainburg & Wang, 2002;Wang & Sainburg, 2003.…”
Section: Differential Control Of Trajectory and Positionmentioning
confidence: 54%
“…This modified access model extends the original access model by proposing that the properties of the controller used after initial memory formation will determine the nature of the information transferred across the limb systems. They further proposed that the two arm controllers have independent (short term) memory resources that can be accessed by their counterpart, based on a finding that adapting to two opposing visuomotor rotations simultaneously by the two arms neither facilitates nor interferes with interlimb transfer (Wang and Sainburg 2003). This idea has been confirmed by other studies, which demonstrated that adaptations to two opposing rotations can coexist in the sensorimotor system, one for each arm (Bock et al 2005;Galea and Miall 2006).…”
Section: Discussionmentioning
confidence: 89%
“…It is suggested that interlimb transfer occurs as a result of the executive decisions made by the motor control system, which occurs subconsciously, to determine whether to access and utilize the information that was obtained during initial learning with, and stored in the memory cache of, the opposite arm (Wang and Sainburg 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies available that looked at the effects of unilateral motor learning on bilateral performance changes using tasks such as visuomotor rotations (Sainburg and Wang, 2002;Taylor et al, 2011;Carroll et al, 2014;Wang and Sainburg, 2003) or ballistic type of movements (Carroll et al, 2013). Up until recently, no study ever looked at potential interference effects of unilateral motor learning.…”
Section: Cross-limb Transfermentioning
confidence: 99%